Inverkansrekvisitets betydelse vid klander av skiljedom - Kuisma,Klara (2024)
The arbitration procedure is a private alternative dispute resolution method aimed at quickly and definitively resolving disputes without external oversight. From this perspective, it is important that the arbitration is not followed by a prolonged and public court process. Arbitral awards, therefore, cannot be appealed on substantive grounds. However, for the arbitration to be a legally secure and acceptable alternative to judicial review, certain fundamental procedural safeguards and formal requirements must be met. In the case of serious procedural errors, an arbitral award can thus be challenged in accordance with the provisions of Section 34 of the Swedish Arbitration Act. The number of challenge proceedings is steadily increasing, and the most frequently invoked grounds for challenge are exceeding the mandate and procedural errors. With the aim of reducing the number of arbitral awards being challenged and thereby maintaining the underlying purpose of the arbitration, an impact requirement was introduced for the grounds of challenge relating to excess of mandate and procedural errors. The impact requirement stipulates that an arbitral award may only be set aside in cases where an excess of mandate or procedural error has likely influenced the outcome of the case. The purpose of this thesis is to investigate the significance of the impact requirement when challenging an arbitral award. The aim is to clarify the legal situation regarding the interpretation and application of the impact requirement. Within the framework of this purpose, the application of the impact requirement will be critically examined to clarify how its application aligns with the underlying purposes of the arbitration and the requirement on the rule of law. Against this background, the thesis intends to answer the following questions: how is the impact requirement interpreted and applied by the Supreme Court and the Svea Court of Appeal (1), and how should the impact requirement be interpreted and applied (2). The thesis concludes that the Supreme Court and the Svea Court of Appeal interpret and apply the impact requirement rather restrictively. The courts have stated that only qualified errors that have had a reasonable impact on the challenge applicant, and where there is a clear link between the error and the out-come, should be considered as having influenced the outcome of the case, thus leading to the annulment of the award. For certain more serious procedural errors and exceeding of the mandate, where it can be questioned whether the procedure was conducted in an acceptable manner, the courts presume that the error has influenced the outcome. It is not entirely clear whether the impact requirement should be applied in the same way for exceeding the mandate and procedural errors. A lack of guidance in the legislative history, conflicting statements in legal doctrine, and a lack of case law make it difficult to draw clear and secure conclusions. However, the thesis concludes that the impact requirement should be applied in the same way for both grounds of challenge.
Keywords: civilrätt; civilprocessrätt; processrätt; skiljedomsrätt; skiljeförfarande; klander; rättstillämpning i skiljeförfarande; inverkansrekvisitet